Progressive multifocal leukoencephalopathy in a patient with multiple myeloma: a case report and analysis of the FDA adverse event reporting system - Jonasson, Elise; Antulov, Ronald; Trøllund Pedersen, Per; Sejbæk, Tobias (Frontiers in Neurology, 2023)
This paper demonstrates a case of progressive multifocal leukoencephalopathy (PML) in a patient with multiple myeloma (MM) treated with nine different MM therapies. This case report contributes to the already published 16 cases of PML in patients with MM. Additionally, this paper presents an analysis of cases from the United States Food and Drug Administration Adverse Event Report System database (n = 117) with a description of demographics and MM-specific therapies. Patients with MM, that developed PML, were treated with immunomodulatory drugs (97%), alkylating agents (52%), and/or proteasome inhibitors (49%). Prior to PML diagnosis, 72% of patients received two or more MM therapies. These results indicate that PML in MM is underreported and could be related to treatment with multiple immunosuppressive therapies rather than MM as a disease itself. Physicians should be aware of potential PML in the late stage of heavily treated MM patients.